Tindak Tutur pada Thomas Shelby dalam Peaky Blinders Musim 1: Analisis Karakter - Taufik Nur Rahman; Deny Kuswahono; Shanty Duwila (EL2J (English Language and Literature Journal), 2023)
This research aims to conduct a speech acts analysis performed by the character of Thomas Shelby in Peaky Blinders Series Season 1. The study seeks to explore the different types of speech acts used by Thomas Shelby and their corresponding meanings. A descriptive qualitative method is employed for this research. Data collection involves the following steps: (1) Carefully and repeatedly watching Peaky Blinders Season 1 on Netflix, (2) Reading the script of Peaky Blinders Series Season 1, (3) Identifying and extracting data from the series' movie scenes and script, (4) Analysing the collected data. The data analysis process includes displaying, defining, classifying, discussing, and drawing conclusions based on the findings. The analysis of Thomas Shelby's speech acts in Peaky Blinders Series Season 1 reveals intriguing patterns in his communication style. Primarily employing assertive speech acts, Thomas displays confidence and strategic leadership in managing the family's illicit activities. Additionally, commissive speech acts demonstrate his sense of responsibility and loyalty through promises and commitments. Expressive speech acts provide insight into his emotions, wit, and humour, contributing to his multifaceted personality. Explicit declarations, however, appear to be absent, which could be attributed to the specific dialogues examined. This analysis sheds light on Thomas Shelby's communication style and its influence on the dynamics within his family and criminal endeavours. Further research could explore the evolution of his speech acts and character in subsequent seasons, providing more in-depth insights into his development as a character.